Electrolyte additive, electrolyte, battery and electronic equipment
By using nitrogen-containing compounds and polynitrile compounds as electrolyte additives in lithium-ion batteries, the problem of deterioration of battery cycle performance and storage performance under high operating voltage is solved, and higher mechanical strength and lithium ion mobility are achieved, reducing side reactions.
Patent Information
- Application Number
- CN202411982760.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
At high operating voltage, the circulation and storage performance of lithium-ion batteries are deteriorated, and existing additives cannot completely suppress side reactions.
Nitrogen-containing compounds and polynitrile compounds are used as electrolyte additives. The nitrogen-containing compounds participate in the construction of the negative electrode interface film through a ring-opening reaction. The polynitrile compounds are complexed and adsorbed with the transition metal in the positive electrode active material to prevent their dissolution.
It improves the circulation and storage performance of the battery, enhances the mechanical strength and lithium ion mobility of the negative electrode interface film, and reduces the structural phase change and interface side reaction of the positive electrode active material.
Smart Images

Figure BDA0005221995650000021 
Figure BDA0005221995650000022 
Figure BDA0005221995650000031
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrolyte additives, electrolytes, batteries and electronic equipment. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, new energy vehicles, energy storage, etc. With the rapid development of the new energy vehicle industry, consumers have higher requirements for driving range and application scenarios, that is, batteries have higher energy density.
[0003] In order to improve the energy density of the battery, one of the methods is to increase the operating voltage of the battery. However, under high operating voltage, some side reactions will occur inside the battery, such as structural phase change of the positive electrode active material, dissolution of transition metals, intensified interface side reactions between the positive electrode active material and the electrolyte, insufficient stability of the positive and negative electrode interface films of the battery, and decomposition, which will lead to the degradation of the battery's cycle performance and storage performance. At present, a large number of additives have been reported to solve the above problems, such as ethylene carbonate, 1,3-propane sulfonone, fluoroethylene carbonate and adiponitrile, etc. However, these additives cannot completely inhibit the above side reactions.
[0004] Therefore, those skilled in the art are in urgent need of developing an electrolyte additive that can improve the cycle performance and storage performance of batteries at high voltages. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides an electrolyte additive, an electrolyte, a battery and an electronic device, which can improve the cycle performance and storage performance of the battery.
[0006] In a first aspect, the present application provides an electrolyte additive, wherein the electrolyte additive includes a first additive; the first additive includes a nitrogen-containing compound and a polynitrile compound, and the polynitrile compound includes a first nitrile additive and / or a second nitrile additive; wherein,
[0007] The structural formula of the nitrogen-containing compound is as follows:
[0008]
[0009] Wherein, R1 and R2 are each independently selected from one of a H atom and a C1-C8 alkyl group;
[0010] The structural formula of the first nitrile additive is as follows:
[0011] NC-R3-O-R4-O-R5-CN
[0012] Formula 2
[0013] In Formula 2, R3, R4, and R5 are each independently selected from substituted or unsubstituted C1-C8 alkylene groups, wherein the substituent is selected from C1-C8 alkyl groups containing cyano and alkoxy groups;
[0014] The structural formula of the second nitrile additive is as follows:
[0015] NC-R6-CN
[0016] Formula 3
[0017] In Formula 3, R6 is selected from substituted or unsubstituted C1-C10 alkylene groups, substituted or unsubstituted C2-C10 olefinene groups, wherein the substituent is selected from at least one of C1-C8 alkyl groups, C2-C8 olefin groups, and cyano groups.
[0018] The electrolyte additive as described above, wherein the nitrogen-containing compound includes a compound represented by Formula 1-1 and / or Formula 1-2:
[0019]
[0020] And / or, the first nitrile additive of Formula 2 includes a compound represented by Formula 2-1 and / or Formula 2-2:
[0021]
[0022] And / or, the second nitrile additive of Formula 3 includes at least one of the compounds represented by Formula 3-1 to Formula 3-10:
[0023]
[0024]
[0025] The electrolyte additive as described above, wherein the mass percentage of the nitrogen-containing compound in the electrolyte is 0.1% to 4%;
[0026] The mass percentage of the polynitrile compound in the electrolyte is 2% to 6%.
[0027] The electrolyte additive as described above, wherein the mass percentage of the first nitrile additive in the electrolyte is 0.1% to 2%;
[0028] The mass percentage of the second nitrile additive in the electrolyte is 2% to 6%.
[0029] The electrolyte additive as described above, wherein the electrolyte additive further includes a second additive, and the second additive includes a compound shown in Formula 4:
[0030]
[0031] Wherein, R7 and R8 are each independently selected from H, a substituted or unsubstituted cyclic carbonate group, and a substituted or unsubstituted cyclic sulfate group.
[0032] The electrolyte additive as described above, wherein the second additive comprises at least one of the compounds represented by Formula 4-1 to Formula 4-5:
[0033]
[0034]
[0035] The electrolyte additive as described above, wherein the mass ratio of the first additive to the second additive is (0.1-8):(0.1-8); preferably, the mass ratio of the first additive to the second additive is (1-4):(1-4).
[0036] The electrolyte additive as described above, wherein, further comprises one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, propylene sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, pentafluoroethoxyphosphazene, dicyclohexylcarbonyl, trimethyl imide phosphate, and hexamethylene diisocyanate.
[0037] A second aspect of the present application provides an electrolyte, which includes an organic solvent, an electrolyte additive and an electrolyte salt, wherein the electrolyte additive is the electrolyte additive as described above.
[0038] The electrolyte as described above, wherein the mass percentage of the organic solvent in the electrolyte is 20% to 80%; and / or,
[0039] The organic solvent comprises one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl propionate, propyl propionate, ethyl fluoroacetate, ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, γ-butyrolactone, sulfolane, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, methyl acrylate, ethyl acrylate, etc.; and / or,
[0040] The mass percentage of the electrolyte salt in the electrolyte is 10% to 30%; and / or,
[0041] The electrolyte salt includes one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium cyano(trifluoromethanesulfonyl)imide; and / or
[0042] The mass percentage of the electrolyte additive in the electrolyte is 5% to 35%.
[0043] A third aspect of the present application provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte as described above.
[0044] The battery as described above, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of lithium cobalt oxide, lithium manganese oxide, and nickel cobalt lithium manganese oxide;
[0045] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material includes at least one of graphite, hard carbon, silicon, silicon oxide compounds, and silicon carbon compounds.
[0046] The technical solution provided by the present application may include the following beneficial effects: when the electrolyte additive includes a first additive, and the first additive includes a nitrogen-containing compound having structural formula 1 and a polynitrile compound, and the polynitrile compound includes a first nitrile additive having structural formula 2 and / or a second nitrile additive having structural formula 3, the nitrogen-containing compound and the polynitrile compound act synergistically. On the one hand, the nitrogen heterocyclic structure contained in the nitrogen-containing compound can undergo a ring-opening reaction, participate in the construction of the negative electrode interface film, effectively promote the increase of the inorganic content in the negative electrode interface film, and improve the mechanical strength and lithium ion mobility of the negative electrode interface film, thereby improving the SEI film under high working voltage. Structural stability can prevent the SEI film from rupturing and causing the electrolyte to contact the negative electrode active material, thereby avoiding the side reaction that causes gas production. At the same time, the film formation impedance of the compound is low, which can effectively improve the lithium ion mobility, reduce the internal resistance of the battery, and improve the battery's cycle performance. On the other hand, the polynitrile compound can complex and adsorb with the transition metal in the positive electrode active material to avoid the dissolution of the transition metal, improve the stability of the positive electrode active material, reduce the gas production caused by the oxidation and decomposition of the electrolyte on the surface of the positive electrode active material, and avoid the migration of the transition metal to the negative electrode active material causing damage to the negative electrode interface film, thereby improving the battery's cycle performance and storage performance.
[0047] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0048] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0049] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0050] In the related art, when the battery is under high voltage environment, the side reactions of the positive electrode active material increase, such as structural phase change of the positive electrode active material, dissolution of transition metals, intensified interface side reactions between the positive electrode active material and the electrolyte, insufficient stability of the positive and negative electrode interface films of the battery and decomposition, etc., which leads to the degradation of the battery's cycle performance and storage performance.
[0051] In view of the above problems, an embodiment of the present application provides an electrolyte additive, wherein the electrolyte additive includes a first additive; the first additive includes a nitrogen-containing compound and a polynitrile compound, and the polynitrile compound includes a first nitrile additive and / or a second nitrile additive; wherein,
[0052] The structural formula of nitrogen-containing compounds is as follows:
[0053]
[0054] In Formula 1, R1 and R2 are each independently selected from one of a H atom and a C1-C8 alkyl group;
[0055] The structural formula of the first nitrile additive is as follows:
[0056] NC-R3-O-R4-O-R5-CN
[0057] Formula 2
[0058] In Formula 2, R3, R4, and R5 are each independently selected from substituted or unsubstituted C1-C8 alkylene groups, wherein the substituent is selected from C1-C8 alkyl groups containing cyano and alkoxy groups;
[0059] The structural formula of the second nitrile additive is as follows:
[0060] NC-R6-CN
[0061] Formula 3
[0062] In Formula 3, R6 is selected from substituted or unsubstituted C1-C10 alkylene groups, substituted or unsubstituted C2-C10 olefinene groups, wherein the substituent is selected from at least one of C1-C8 alkyl groups, C2-C8 olefin groups, and cyano groups.
[0063] The nitrogen-containing compound of the present application may refer to a compound including a nitrogen heterocyclic structure, such as an oxazolidinone compound; the first nitrile additive of the present application may refer to an additive including a cyano group and an ether group; the second nitrile additive of the present application may refer to an additive including a dicyano group.
[0064] The C1-C8 alkyl group in the present application refers to an alkyl group with 1 to 8 carbon atoms. The substituted or unsubstituted C1-C8 alkylene group in the present application refers to an alkylene group with 1 to 8 carbon atoms that is substituted or unsubstituted, and the C1-C8 alkyl group containing cyano and alkoxy groups refers to an alkyl group with 1 to 8 carbon atoms that includes both cyano and alkoxy substituents; for example, R3, R4, and R5 can be selected from -CH2-, -C2H4-, -C3H6-, -CH-OCH2CN, -CH-OC2H4CN, -CH-OC3H6CN, -CH-OC4H8CN, etc.
[0065] The substituted or unsubstituted C1-C10 alkylene group of the present application refers to an alkylene group with 1 to 10 carbon atoms and a substituted or unsubstituted group; the substituted or unsubstituted C2-C10 olefinene group refers to an olefinene group with 2 to 10 carbon atoms and a substituted or unsubstituted group; wherein the substituents of the alkyl and olefin groups are selected from at least one of C1-C8 alkyl groups, C1-C8 olefin groups, and cyano groups. For example, R6 can be selected from -CH2-, -C2H4-, -C3H6-, -CH=CH-, -CH2CH=CH-, -CH(CN)-, -CH2CH=C(CN)-, etc.
[0066] According to the above scheme provided in the present application, after the electrolyte additive is added to the electrolyte and applied to the battery, the battery has excellent cycle performance and storage performance. The applicant analyzed this principle and believed that the reason is that the nitrogen-containing compound and the polynitrile compound act synergistically. On the one hand, the nitrogen heterocyclic structure contained in the nitrogen-containing compound can undergo a ring-opening reaction, and the oxygen in the nitrogen heterocyclic structure coordinates with lithium ions more quickly, participates in the construction of the negative electrode interface film, and effectively promotes the increase of the inorganic content in the negative electrode interface film, improves the mechanical strength and lithium ion mobility of the negative electrode interface film, thereby improving the structural stability of the SEI film at high operating voltage, avoids the rupture of the SEI film so that the electrolyte contacts the negative electrode active material, thereby avoiding the occurrence of side reactions leading to gas production problems. At the same time, the film formation impedance of the compound is low, which can effectively improve the lithium ion mobility and improve the cycle performance of the battery; on the other hand, the polynitrile compound can complex and adsorb with the transition metal in the positive electrode active material, avoid the dissolution of the transition metal, improve the stability of the positive electrode active material, reduce the gas production caused by the oxidative decomposition of the electrolyte on the surface of the positive electrode active material, and avoid the migration of the transition metal to the negative electrode active material to cause the destruction of the negative electrode interface film, thereby improving the cycle performance and storage performance of the battery.
[0067] In a specific embodiment, the nitrogen-containing compound includes a compound represented by Formula 1-1 and / or Formula 1-2:
[0068]
[0069] When the nitrogen-containing compound is selected from the compounds shown in Formula 1-1 and / or Formula 1-2, the nitrogen-containing additive can participate in the construction of the negative electrode interface film, further improve the mechanical properties and lithium conductivity of the negative electrode interface film, and avoid the side reaction between the negative electrode active material and the electrolyte causing the electrolyte to decompose and produce gas, thereby further improving the battery's cycle performance and storage performance.
[0070] In a specific embodiment, the first nitrile additive of Formula 2 includes a compound represented by Formula 2-1 and / or Formula 2-2:
[0071]
[0072]
[0073] When the nitrile additive is selected from the compounds shown in Formula 2-1 to Formula 2-2, it can better complex and adsorb the transition metals in the positive electrode active material to avoid the dissolution of the transition metals in the positive electrode active material. At the same time, the nitrile additive can participate in the construction of the positive electrode interface film and enhance the stability of the positive electrode interface film, thereby further improving the battery's cycle performance and storage performance.
[0074] In a specific embodiment, the second nitrile additive of Formula 3 includes at least one of the compounds shown in Formula 3-1 to Formula 3-10:
[0075]
[0076]
[0077] When the second nitrile additive is a compound shown in Formula 3-1 to Formula 3-10, the second nitrile additive can better complex and adsorb the transition metal in the positive electrode active material, avoid the dissolution of the transition metal in the positive electrode active material, avoid damage to the negative electrode interface film and decomposition and gas production of the electrolyte, thereby further improving the battery's cycle performance and storage performance.
[0078] In a specific embodiment, the mass percentage of the nitrogen-containing compound in the electrolyte is 0.1% to 4%, for example, the mass percentage of the nitrogen-containing compound in the electrolyte can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, etc.; the mass percentage of the polynitrile compound in the electrolyte is 2% to 6%, for example, the mass percentage of the polynitrile compound in the electrolyte can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%, etc. When the mass percentages of the nitrogen-containing compound and the polynitrile compound in the electrolyte are respectively within the above ranges, the nitrogen-containing compound and the polynitrile compound can better synergize, further improve the stability of the positive and negative electrode interface film and the lithium ion mobility, and can better complex and adsorb the transition metal in the positive electrode active material, thereby reducing the side reactions of the battery and improving the battery's cycle performance and storage performance to a greater extent.
[0079] In a specific embodiment, the mass percentage of the first nitrile additive in the electrolyte is 0.1% to 2%, for example, the mass percentage of the first nitrile additive in the electrolyte is 0.1%, 0.5%, 1%, 1.5% or 2%, etc.; the mass percentage of the second nitrile additive in the electrolyte is 2% to 6%, for example, the mass percentage of the second nitrile additive in the electrolyte is 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%, etc. When the mass percentage of the first nitrile additive and the second nitrile additive in the electrolyte is within the above range, the first nitrile additive and the second nitrile additive can act synergistically, can better complex and adsorb the transition metal in the positive electrode active material, reduce the dissolution of the transition metal, further improve the stability of the positive electrode active material, and can better improve the stability of the positive electrode interface, so that the cycle performance and storage performance of the battery are better.
[0080] In a specific embodiment, the electrolyte additive further includes a second additive, and the second additive includes a compound shown in Formula 4:
[0081]
[0082] Wherein, R7 and R8 are each independently selected from H, a substituted or unsubstituted cyclic carbonate group, and a substituted or unsubstituted cyclic sulfate group.
[0083] The substituted or unsubstituted cyclic carbonate group of the present application refers to a group including -OC(=O)-O- with a substituent or an unsubstituted group, for example The substituted or unsubstituted cyclic sulfate group of the present application refers to a group including -OS(=O)2-O- with a substituent or an unsubstituted group, for example wait.
[0084] The second additive of the present application includes a cyclic carbonate group and a cyclic sulfate group, and the cyclic carbonate group or the cyclic sulfate group can participate in the formation of the positive and negative electrode interface film and improve the stability of the positive and negative electrode interface film. When the second additive is selected from the compound of formula 4, the first additive and the second additive can work synergistically to generate a more stable positive and negative electrode interface film, improve the stability of the positive and negative electrode active materials, and decompose and produce gas problems. At the same time, the second additive has high compatibility with the electrolyte, making the electrolyte more stable, avoiding the electrolyte from undergoing redox reactions on the surface of the positive and negative electrode active materials, thereby greatly improving the cycle performance and storage performance of the battery.
[0085] In a specific embodiment, the second additive includes at least one of the compounds shown in Formula 4-1 to Formula 4-5:
[0086]
[0087]
[0088] When the second additive is a compound shown in Formula 4-1 to Formula 4-5, the synergistic effect of the first additive and the second additive is higher, so that the stability of the negative electrode interface film is better, the protection of the positive and negative electrode active materials is higher, and the side reactions of the positive and negative electrode active materials are avoided. It can also further improve the stability of the electrolyte, avoid the decomposition and gas production of the electrolyte, and make the battery cycle performance and storage performance better.
[0089] In a specific embodiment, the mass ratio of the first additive to the second additive is (0.1-8):(0.1-8), preferably, the mass ratio of the first additive to the second additive is (1-4):(1-4), for example, the mass ratio is 0.1:0.5, 0.1:1, 0.1:2, 0.1:4, 0.1:8, 8:0.1, 4:0.4, 2:0.1, 0.5:0.1, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 2:3, 3:2, etc. When the mass ratio of the first additive and the second additive is within the above range, the synergistic effect of the first additive and the second additive is better, the negative electrode interface film generated by the first additive has higher mechanical properties and lower impedance, and the complexation and adsorption effects on the positive electrode transition metal are better, thereby avoiding the dissolution of the transition metal and improving the stability of the positive and negative electrode active materials. At the same time, it can improve the stability of the electrolyte and avoid the decomposition and gas production of the electrolyte, so that the battery exhibits excellent cycle performance and storage performance.
[0090] In a specific embodiment, the mass percentage of the first additive in the electrolyte is 0.1% to 8%, for example, the mass percentage is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%. When the mass percentage of the first additive is within the above range, the stability of the negative electrode interface film formed by the first additive and the second additive is better, and the impedance is lower. At the same time, the complexation and adsorption effect with the positive electrode transition metal is better, which is conducive to reducing the dissolution of the transition metal and improving the stability of the positive and negative electrodes, thereby effectively improving the cycle performance and storage performance of the battery. Preferably, the mass percentage of the first additive in the electrolyte is 1% to 4%.
[0091] In a specific embodiment, the mass percentage of the second additive in the electrolyte is 0.1% to 8%, for example, the mass percentage is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%. When the mass percentage of the second additive is within the above range, the second additive and the first additive are better coordinated, and the mechanical properties and lithium conductivity of the generated negative electrode interface film are higher. At the same time, the stability of the electrolyte is higher, which is conducive to reducing the decomposition and gas production of the electrolyte on the surface of the positive and negative electrodes, and avoiding the deterioration of the cycle performance and storage performance of the battery. Preferably, the mass percentage of the second additive in the electrolyte is 1% to 4%.
[0092] In a specific embodiment, the electrolyte additive also includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, propene sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, pentafluoroethoxyphosphazene, dicyclohexylcarbonyl, imide trimethyl phosphate, hexamethylene diisocyanate, etc. Preferably, the electrolyte additive includes fluoroethylene carbonate. When the electrolyte additive also includes the above-mentioned compound, the above-mentioned compound can synergize with the first additive and the second additive to further enhance the stability and lithium conductivity of the negative electrode interface film, thereby better protecting the negative electrode active material and the electrolyte, avoiding side reactions of the negative electrode active material and the electrolyte, and making the battery cycle performance and storage performance better.
[0093] The second aspect of the present application provides an electrolyte comprising the above electrolyte additive. The electrolyte is applied to a battery to improve the cycle performance and storage performance of the battery.
[0094] In a specific embodiment, the electrolyte includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl propionate, propyl propionate, ethyl fluoroacetate, ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, methyl acrylate, and ethyl acrylate, and the mass percentage of the organic solvent in the electrolyte is 20% to 80%, for example, the mass percentage is 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc. When the organic solvent of the electrolyte is selected from the above organic solvent, the viscosity of the electrolyte is lower and the ion conductivity is higher, which is beneficial to improving the migration rate of lithium ions. In addition, the above organic solvent can improve the stability of the electrolyte and avoid decomposition reactions of the electrolyte, thereby further improving the cycle performance and storage performance of the battery.
[0095] In a specific embodiment, the electrolyte includes an electrolyte salt, and the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bisoxalate borate, lithium difluorobisoxalate phosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium cyano(trifluoromethanesulfonyl)imide; the mass percentage of the electrolyte salt in the electrolyte is 10% to 30%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, etc. When the selection of the electrolyte salt and the mass percentage are within the above range, the conductivity and stability of the electrolyte can be further improved, thereby further improving the cycle performance and storage performance of the battery.
[0096] In a specific embodiment, the mass percentage of the electrolyte additive in the electrolyte is 5% to 35%, for example, the mass percentage is 5%, 10%, 15%, 20%, 25%, 30% or 35%, etc. When the selection and mass percentage of the electrolyte additive are within the above range, the electrolyte additive can give full play to its performance, improve the stability and lithium conductivity of the positive and negative electrode interface film, and improve the stability of the positive electrode active material, so as to better protect the positive and negative electrode active materials and the electrolyte, avoid the side reactions of the positive electrode active material, the negative electrode active material, and the electrolyte, and make the battery cycle performance and storage performance better.
[0097] The third aspect of the present application provides a battery comprising the above electrolyte, which exhibits excellent cycle performance and storage performance.
[0098] In a specific embodiment, the battery includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, and nickel cobalt manganese oxide. Preferably, the positive electrode active material includes lithium cobalt oxide and / or nickel cobalt manganese oxide. When the positive electrode active material is selected from the above compounds, the positive electrode active material can give full play to its performance and improve the electrochemical performance of the battery.
[0099] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0100] In a specific embodiment, the battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active material comprises at least one of graphite, hard carbon, silicon, silicon oxide compounds and silicon carbon compounds. Preferably, the negative electrode active material comprises silicon.
[0101] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0102] The conductive agent and the binder in the positive electrode active material layer and the negative electrode active material layer of the embodiment of the present application can be conventional materials in the art.
[0103] In a specific embodiment, the battery also includes a diaphragm. The embodiment of the present application has no particular restrictions on the material and shape of the diaphragm, as long as it does not significantly damage the effect of the present application. It may include porous sheet-like or non-woven fabric-like materials with excellent liquid retention, etc. The materials of the resin or glass fiber diaphragm include but are not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc., and can be specifically set according to needs.
[0104] Hereinafter, the present application will be further described in detail through specific embodiments.
[0105] Example 1
[0106] 1. Preparation of positive electrode
[0107] The positive electrode active material lithium cobalt oxide (LCO), the conductive agent CNT, and the adhesive PVDF are fully stirred and mixed in NMP solvent at a weight ratio of 97:1.5:1.5. The slurry is coated on an aluminum foil with a safety primer. After drying, cold pressing, slitting, sheet making, welding, and lug gluing, a positive electrode sheet that meets the winding requirements is made.
[0108] 2. Preparation of negative electrode sheet
[0109] The negative electrode active material (graphite and carbon-coated silicon material, in which the silicon content is 10%), the binder (SBRCMC) and the conductive agent (carbon black) are added to the water as a solvent at a weight ratio of 95:3.5:1.5 to prepare the negative electrode slurry. The slurry is coated on the negative electrode current collector Cu foil, and after drying, cold pressing, stripping, sheeting welding, and lug gluing, the negative electrode sheet that meets the winding requirements is made.
[0110] 3. Preparation of electrolyte
[0111] Ethylene carbonate (EC), propylene carbonate (PC), ethyl propionate (EP) and propyl propionate (PP) are mixed and stirred in a mass ratio of 1.5:1.5:4:3 to form a mixed solvent, and 16% of lithium hexafluorophosphate (LiPF6) is added and mixed evenly; then, based on the total mass of the electrolyte, 10% of fluoroethylene carbonate (FEC) is added, and the first additive and the second additive are added (the types and amounts of the additives are shown in Table 1) to obtain the electrolytes of the embodiments and comparative examples.
[0112] 4. Production of lithium-ion batteries
[0113] The positive electrode sheet, separator and negative electrode sheet are wound to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched to complete the top and side sealing. After high-temperature baking, the prepared electrolyte is injected, and then the battery is completed after standing, forming, volume separation, testing and other processes.
[0114] The preparation methods of the batteries provided in Examples 2 to 56 and Comparative Examples 1 to 31 are substantially the same as that in Example 1, and the specific parameters are shown in Table 1.
[0115] Table 1
[0116]
[0117]
[0118]
[0119]
[0120] Test example
[0121] Battery performance test:
[0122] 45℃ cycle test: The battery is placed at 45℃ for 4h, charged to 4.53V at 1C constant current, cut-off current 0.05C, placed for 10min, and the initial internal resistance R0, full-charge thickness and charging capacity are tested. Discharge at 0.5C to 3.0V, record the discharge capacity C0 as the initial value, repeat for 200 cycles, and test the full-charge internal resistance and full-charge thickness every 100 cycles. The final capacity C of 200 cycles is 200 、Internal resistance R 200 , thickness D 200 , then, capacity retention rate = C 200 / C0, internal resistance growth rate = R 200 / R0-1, thickness change rate = D 200 / D0-1, the results are recorded in Table 2.
[0123] 80℃ storage test: the battery is charged to 4.53V at 0.5C constant current, with a cut-off current of 0.05C, and left to stand for 10 minutes. The fully charged thickness D0 is tested. The battery is left to stand at 85±2℃ for 6 hours with an open circuit and the hot thickness D1 is tested immediately after it is taken out of the box. Thickness change rate = D1 / D0-1.
[0124] Table 2
[0125]
[0126]
[0127]
[0128]
[0129] It can be seen from Table 2 that, according to the comparison between Examples 1 to 13 and Comparative Examples 1, Comparative Examples 2 to 16, and the comparison between Example 12 and Comparative Example 26, when the first additive includes a nitrogen-containing compound and a polynitrile compound, it is beneficial to improve the cycle performance and storage performance of the battery.
[0130] According to the comparison between Examples 14 to 17 and Comparative Examples 17 and 18, when the mass percentage of the nitrogen-containing compound in the electrolyte is 0.1% to 4%, the nitrogen-containing compound can improve the mechanical strength and lithium ion mobility of the negative electrode interface film, thereby improving the cycle performance and storage performance of the battery.
[0131] According to the comparison between Examples 18 to 20 and Comparative Examples 19 and 20, it can be seen that when the mass percentage of the polynitrile compound in the electrolyte is 2% to 6%, the polynitrile compound can complex and adsorb with the transition metal in the positive electrode active material to avoid the dissolution of the transition metal, thereby improving the stability of the positive electrode active material and making the battery's cycle performance and storage performance better.
[0132] According to the comparison between Examples 21 to 24 and Comparative Examples 21 and 22, when the mass percentage of the first nitrile additive in the electrolyte is 0.1% to 2%, the cycle performance and storage performance of the battery are better.
[0133] According to the comparison between Examples 25 to 27 and Comparative Examples 23 and 24, when the mass percentage of the second nitrile additive in the electrolyte is 2% to 6%, the cycle performance and storage performance of the battery can be further improved.
[0134] According to the comparison between Examples 28 to 33 and Comparative Examples 25 and 26, and between Example 45 and Comparative Examples 28 and 29, it can be seen that when the mass percentage of the first additive in the electrolyte is 0.1% to 8%, the cycle performance and storage performance of the battery can be improved to a greater extent.
[0135] According to the comparison between Examples 34 to 46 and Examples 1 to 13, it can be seen that when the first additive and the second additive act synergistically, it is beneficial to improve the cycle performance and storage performance of the battery.
[0136] According to the comparison between Examples 47 to 52 and Comparative Examples 30 and 31, it can be seen that when the mass percentage of the second additive in the electrolyte is 0.1% to 8%, the cycle performance and storage performance of the battery are better.
[0137] According to the comparison of Examples 53 to 56, when the second additive is selected from the compounds shown in Formula 4-1 to Formula 4-5, the synergistic effect of the first additive and the second additive is higher, so that the stability of the negative electrode interface film is better, and the cycle performance and storage performance of the battery are better.
[0138] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrolyte additive, characterized in that: The electrolyte additive includes a first additive; the first additive includes a nitrogen-containing compound and a polynitrile compound, and the polynitrile compound includes a first nitrile additive and / or a second nitrile additive; wherein, The structural formula of the nitrogen-containing compound is as follows: In Formula 1, R1 and R2 are each independently selected from one of a H atom and a C1-C8 alkyl group; The structural formula of the first nitrile additive is as follows: NC-R3-O-R4-O-R5-CN Formula 2 In Formula 2, R3, R4, and R5 are each independently selected from substituted or unsubstituted C1-C8 alkylene groups, wherein the substituent is selected from C1-C8 alkyl groups containing cyano and alkoxy groups; The structural formula of the second nitrile additive is as follows: NC-R6-CN Formula 3 In Formula 3, R6 is selected from substituted or unsubstituted C1-C10 alkylene groups, substituted or unsubstituted C2-C10 olefinene groups, wherein the substituent is selected from at least one of C1-C8 alkyl groups, C2-C8 olefin groups, and cyano groups.
2. The electrolyte additive according to claim 1, characterized in that: The nitrogen-containing compound includes a compound represented by Formula 1-1 and / or Formula 1-2: And / or, the first nitrile additive of Formula 2 includes a compound represented by Formula 2-1 and / or Formula 2-2: And / or, the second nitrile additive of Formula 3 includes at least one of the compounds represented by Formula 3-1 to Formula 3-10:
3. The electrolyte additive according to claim 1, characterized in that: The mass percentage of the nitrogen-containing compound in the electrolyte is 0.1% to 4%; The mass percentage of the polynitrile compound in the electrolyte is 2% to 6%.
4. The electrolyte additive according to claim 1, characterized in that: The mass percentage of the first nitrile additive in the electrolyte is 0.1% to 2%; The mass percentage of the second nitrile additive in the electrolyte is 2% to 6%.
5. The electrolyte additive according to claim 1, characterized in that: The electrolyte additive further includes a second additive, wherein the second additive includes a compound shown in Formula 4: Wherein, R7 and R8 are each independently selected from H, a substituted or unsubstituted cyclic carbonate group, and a substituted or unsubstituted cyclic sulfate group.
6. The electrolyte additive according to claim 5, characterized in that: The second additive includes at least one of the compounds shown in Formula 4-1 to Formula 4-5:
7. The electrolyte additive according to any one of claims 5 to 6, characterized in that: The mass ratio of the first additive to the second additive is (0.1-8):(0.1-8); preferably, the mass ratio of the first additive to the second additive is (1-4):(1-4).
8. The electrolyte additive according to any one of claims 1 to 5, characterized in that: It also includes one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, propylene sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, pentafluoroethoxyphosphazene, dicyclohexylcarbonyl, trimethyl imide phosphate, and hexamethylene diisocyanate.
9. An electrolyte, characterized in that: The invention comprises an organic solvent, an electrolyte additive and an electrolyte salt, wherein the electrolyte additive is the electrolyte additive according to any one of claims 1 to 8.
10. The electrolyte according to claim 9, characterized in that The mass percentage of the organic solvent in the electrolyte is 20% to 80%; and / or, The organic solvent comprises one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl propionate, propyl propionate, ethyl fluoroacetate, ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, γ-butyrolactone, sulfolane, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, methyl acrylate, ethyl acrylate, etc.; and / or, The mass percentage of the electrolyte salt in the electrolyte is 10%-30%; and / or, The electrolyte salt includes one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium cyano(trifluoromethanesulfonyl)imide; and / or The mass percentage of the electrolyte additive in the electrolyte is 5% to 35%.
11. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to claim 9 or 10.
12. The battery according to claim 11, characterized in that The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of lithium cobalt oxide, lithium manganese oxide, and nickel cobalt lithium manganese oxide; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material includes at least one of graphite, hard carbon, silicon, silicon oxide compounds, and silicon carbon compounds.
Citation Information
Patent Citations
Non-aqueous electrolyte and lithium secondary battery including the same
CN102569886A
Electrolyte and lithium ion battery containing same
CN114300747A
Electrolyte and battery comprising same
CN117374388A
Electrolyte additive, electrolyte and battery
CN118073653A
Electrolyte for nonaqueous secondary battery, nonaqueous secondary battery, and additive for electrolyte
JP2014127354A